Colette has already spent 3 minutes on the phone, and she expects to spend 1 more minutewith every phone call she routes. In all, how many phone calls does Colette have to route
to spend a total of 26 minutes on the phone?

Answers

Answer 1
Answer: If she spends 4 minutes on each call she would need to make 7 calls

Related Questions

Which of the following is a solution of y - x < -3?
Can someone help please!!find the maximum value of function f(x) = -1.1x^2 - 3.6x + 1
Which choice is equivalent to the quotient shown here when x > 0?√50x^2 divide by √32x^2.a.5√x/4b.5x/4c.√18xd.√50x^3-32x^2
Find all numbers such that the square of the number is 48 more than double the number. If you find more than one, then list all the numbers you find in increasing order, separated by commas.?
A group of students surveyed chose baseball and soccer as their favorite sport in the ratio 3:8 A) if 132 students were surveyed, find the number of students that chose soccer as there favorite sport B) if 56 students chose soccer as their favorite sport, find the number of students that chose baseball as their favorite sport.

HELP ASP!!!!!! The explicit rule for a sequence and one of the specific terms is given. Find the position of the given
term.
f(n) = 1.25n +3.75; 20
20 is the
th term.

Answers

Answer:

13th term

Step-by-step explanation:

Answer:

the 13th term, if you plug in 13 for n and solve you would get 20 :)

Simplify sin(180-x)°-sin x°

Answers

Answer:

0

Step-by-step explanation:

sin(180-x) - sin(x)

= sin(180) × cos(x) - cos(180) × sin(x) - sin(x)

= 0 × cos(x) - (-1) × sin(x) - sin(x)

= 0 + sin(x) - sin(x)

= 0

Simplify 10 + 4(x + 1) + 5. User: Simplify 18 - 2[x + (x - 5)].

Answers

10 + 4(x + 1) + 5
10 + 4(x) + 4(1) + 5
10 + 4x + 4 + 5
10 + 4x + 9
10 + 9 + 4x
19 + 4x
4x + 19

18 - 2[x + (x - 5)]
18 - 2(x + x - 5)
18 - 2(2x - 5)
18 - 2(2x) + 2(5)
18 - 4x + 10
-4x + 18 + 10
-4x + 28

A cyclist rode for 3.5 hours and completed a distance of 60.9 miles. If she kept the same average speed for each hour, how far did she ride in 1 hour? Part A Estimate the quotient. Include an equation to show your work. Explain

Answers

Answer:

17.4 miles

Step-by-step explanation:

Step one:

given data

time takent= 3.5hours

distance = 60.9miles

the average speed is given as

Average speed= distance/time

Average speed= 60.9/3.5

Average speed= 17.4mph

Step two:

we are told that the speed was actually maintained, so we used the previous value obatained for the following computation

For a time taken as 1 hour, the distance will be

distance= average speed * time

distance= 17.4*1

distance= 17.4 miles

Answer:

Step-by-step explanation: A cyclist rode for 3.5 hours and completed a distance of 60.9 miles. If she kept the same average speed for each hour, how far did she ride in 1 hour?

In the figure above, lines k, l, and m intersect at a point. If x + y = u + w , which of the following must be true?

Answers

From the given equation we have x=z and t=z. Therefore, option B is the correct answer.

Given that, lines k, l, and m intersect at a point.

What is vertical angle theorem?

Vertical angles theorem or verticallyopposite angles theorem states that two opposite vertical angles formed when two lines intersect each other are always equal (congruent) to each other.

From the given figure,

Using vertical angle theorem, we have

x°=t°

y°=u°

w°=z°

If x + y = u + w, then

x+u=u+z

⇒ x=z

If x + y = u + w, then

t+u=u + z

⇒ t=z

So, x=z and t=z

From the given equation we have x=z and t=z. Therefore, option B is the correct answer.

To learn more about the vertical angle theorem visit:

brainly.com/question/8119520.

#SPJ2

Answer:

B)

Step-by-step explanation:

First, let's write down what we know based on the Vertical Angle Theorem and the info given by the question:

1. Vertical angle theorem claims that opposite angles are the same, therefore:

  • y=u
  • x=t
  • w=z

2. We know from the problem that:

  • x+y = u+w

3. Now for the proofing:

Since  x+y = u+w, let us try to cross off the variable u and see if we can get x equaling to w.

We know that y=u, so let us switch out y for another u, allowing the same variable to cross out

x+y = u+w --> x+u = u+w --> x=w

Ok now we know x=w, and recall that w=z. So x would also equal to z!

Let us try to proof z=t:

We know that x=t

But now we also know that x=z (from previous)

Therefore we can substitute the z in for x in x=t and voila z=t!

Try finding out if y=w. No matter how many equations you create, they are not the same. It would not make sense either if you use this equation: x+y = u+w. If w and x are the same then y cannot be anything except being equal to "u". We cannot prove that u is equal to anything else either.

Therefore the answer is B)

Prove that: (a2 - b2)3 + (b2-c2)3+ (c2-a2)3 = 3 (a+b) (b+c) (c+a) (a-b) (b-c) (c-a).

Answers

L=(a^2-b^2)^3+(b^2-c^2)^3+(c^2-a^2)^3=(*)\n\n(a^2-b^2)^3=a^6-3a^4b^2+3a^2b^4-b^6\n\n(b^2-c^2)^3=b^6-3b^4c^2+3b^3c^4-c^6\n\n(c^2-a^2)^3=c^6-3c^4a^2+3c^2a^4-a^6\n\n(*)=a^6-3a^4b^2+3a^2b^4-b^6+b^6-3b^4c^2+3b^2c^4-c^6+c^6-\dots\n\dots-3c^4a^2+3c^2a^4-a^6\n\n=-3a^4b^2+3a^2b^4-3b^4c^2+3b^2c^4-3c^4a^2+3c^2a^4\n\n=3(-a^4b^2+a^2b^4-b^4c^2+b^2c^4-a^2c^4+a^4c^2)

R=3(a+b)(a-b)(b+c)(b-c)(c+a)(c-a)\n\n=3(a^2-b^2)(b^2-c^2)(c^2-a^2)\n\n=3(a^2b^2-a^2c^2-b^4+b^2c^2)(c^2-a^2)\n\n=3(a^2b^2c^2-a^4b^2-a^2c^4+a^4c^2-b^4c^2+a^2b^4+b^2c^4-a^2b^2c^2)\n\n=3(-a^4b^2+a^2b^4-b^4c^2+b^2c^4-a^2c^4+a^4c^2)\n\nL=R

(a^2 - b^2)^3 + (b^2 - c^2)3 + (c^2 - a^2)^3 = 3(a + b)(b +c)(c + a)(a - b)(b - c)(c - a)
(a^2 - b^2)^3 + (b^2 - c^2)3 + (c^2 - a^2)^3 = 3(a + b)(a - b)(b + c)(b - c)(c + a)(c - a)
(a^2 - b^2)^3 + (b^2 - c^2)3 + (c^2 - a^2)^3 = 3(a^2 - b^2)(b^2 - c^2)(c^2 - a^2)

(a^2 - b^2)^3 = (a^2 - b2)(a^2 - b^2)(a^2-b^2) = a^6 - 3a^4b^2 + 3a^2b^4 - b^6
(b^2 - c^2)^3 = (b^2 - c^2)(b^2 - c^2)(b^2 - c^2) = b^6 - 3^4c^2 + 3b^2c^4 - c^6)
(c^2 - a^2)^3 = (c^2 - a^2)(c^2 - a^2)(c^2 - a^2) = c^6 - 3a^2c^4 + 3a^4c^2 - a^6

a^6 - 3a^4b^2 + 3a^2b^4 - b^6 + b^6 - 3b^4c^2 + 3b^2c^4 - c^6 + c^6 - 3a^2c^4 + 3a^4c^2 - a^6
-3a^4b^2 + 3a^2b^4 - 3b^4c^2 + 3b^2c^4 - 3a^2c^4 + 3a^4c^2
3(-a^4b^2 + a^2b^4 - b^4c^2 + b2^c^4 - a^2c^4 + a^4c^2)

3(a^2 - b^2)(b^2 - c^2)(c^2 - a^2) = 3(-a^4b^2 + a^2b^4 - b^4c^2 + b^2c^4 - a^2c^4 + a^4c^2)

3(-a^4b^2 + a^2b^4 - b^4c^2 + b^2c^4 - a^2c^4 + a^4c^2) = 3(-a^4b^2 + a^2b^4 - b^4c^2 + b^2c^4 - a^2c^4 + a^4c^2